2020
DOI: 10.3389/fneur.2020.00628
|View full text |Cite
|
Sign up to set email alerts
|

Air vs. Road Decision for Endovascular Clot Retrieval in a Rural Telestroke Network

Abstract: Background and Purpose: Telestroke aims to increase access to endovascular clot retrieval (ECR) for rural areas. There is limited information on transfer workflow for ECR in rural settings. We sought to describe the transfer metrics for ECR in a rural telestroke network with respect to decision making. Methods: A retrospective cohort study was employed on consecutive patients transferred to the comprehensive stroke center (CSC) for ECR in a rural hub-and-spoke telestroke network between April 2013 and October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Of note, “door-to-reperfusion treatment delivery” time in rural NSW Australia hospitals is >100 min ( 6 ), whereas guidelines target <60 min (and ideally <45 min) ( 7 ). Similarly, transfers from rural hospitals to comprehensive specialized stroke centers for endovascular clot retrieval have median “door-in-door-out” times of 214 min ( 8 ). In a 2019 Australian National Stroke Audit, only 52% of stroke patients in Australia were assessed using a validated stroke screen upon arrival in the emergency department, while only around 10% of stroke patients received intravenous thrombolysis (IVT) treatment and 32% of patients were treated within 60 min of arrival at the hospital ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, “door-to-reperfusion treatment delivery” time in rural NSW Australia hospitals is >100 min ( 6 ), whereas guidelines target <60 min (and ideally <45 min) ( 7 ). Similarly, transfers from rural hospitals to comprehensive specialized stroke centers for endovascular clot retrieval have median “door-in-door-out” times of 214 min ( 8 ). In a 2019 Australian National Stroke Audit, only 52% of stroke patients in Australia were assessed using a validated stroke screen upon arrival in the emergency department, while only around 10% of stroke patients received intravenous thrombolysis (IVT) treatment and 32% of patients were treated within 60 min of arrival at the hospital ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with emergent LVO, long DIDO time seems to have a deleterious effect on outcome and may be the most important modifiable factor in onset to recanalization time in a PSC [14,23]. Although longer median times have been reported [17,19,24], it has recently been shown that it is possible to achieve a median DIDO time of 60 minutes [19]. In this case report on three AIS patients with very short time intervals, we did not study the median DIDO time, which may constitute a weakness.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] A quality improvement programme in the state of Victoria has shown that it is possible to obtain a median door in door out (DIDO) time of <60 min 41 for EVT transfers from a metropolitan primary stroke centre (PSC) using a hub and spoke model of care, and a study in rural New South Wales points towards transport modality (air vs road) and associated procedures as important predictors of faster DIDO times. 32 While DIDO target times have been developed for myocardial infarction, there is currently no consensus-based DIDO target time for acute stroke.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“… 31 In rural areas, delays to the initiation of thrombectomy are generally between 4 and 6 hours. 32 Even in urban areas, interhospital transfers are often slow, with a median transfer time of 2 hours. 33 Furthermore, patients who initially present to an EVT-capable centre generally experience a waiting time of at least 60 min between hospital arrival and when thrombectomy can be performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation